Strategic Enhancement of Farmers' Economic Welfare through the Reformulation of Organic Fertilizer Based on Agricultural and Livestock Waste in Bangsring Village, Banyuwangi: Strategi Peningkatan Ekonomi Petani melalui Reformulasi Pupuk Organik Berbasis Limbah Pertanian dan Peternakan di Desa Bangsring, Banyuwangi - dwi priyadi; Meireni Cahyowati; Mohamad Ilham Hilal (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Smallholder farmers require substantial quantities of fertilizer; however, they often fail to optimally utilize the abundant local resources available in their environment, such as livestock manure and agricultural waste. This study aims to analyze fertilizer-related challenges faced by smallholder farmers and provide strategic recommendations to enhance self-sufficiency and improve their economic welfare. A questionnaire regarding the use of organic fertilizer was distributed to members of the Bangsring Sejahtera Farmer Group in Banyuwangi. Survey results indicated that all members had heard of organic fertilizer, yet only 20% were familiar with its production process. Furthermore, the majority (80%) of respondents owned livestock and cultivated agricultural land, suggesting a significant availability of unprocessed raw materials for fertilizer production. An organic fertilizer training program was conducted, incorporating pre-test and post-test assessments. The Wilcoxon test revealed a statistically significant improvement in farmers’ knowledge, with a median score increase from 5 (pre-test) to 7 (post-test). The utilization of livestock and agricultural waste—comprising 50% goat/sheep manure, 25% cattle manure, 10% poultry manure, and 15% agricultural residues (coconut husks, rice husks, straw)—resulted in high-quality fertilizer. Training on the use of manure shredders, fertilizer sieves, and branded packaging enhanced production efficiency, improved fertilizer quality, and increased market value. The selling price of fertilizer rose from IDR 800/kg (without modern processing) to IDR 3.300/kg following proper grinding, sieving, and packaging. This directly contributed to increased income for the farmer group.